Innervated Free Flap Abdominal Wall Reconstruction: A Systematic Review - Therattil, Paul J.; Viviano, Stephen L.; Lee, Edward S.; Keith, Jonathan D. (Journal of Reconstructive Microsurgery Open, 2017)
Background Reconstruction of large abdominal wall defects provides unique challenges to the plastic surgeon. Reconstruction with innervated free flaps has been described and allows for true functional replacement of “like with like.” The authors sought to determine the frequency and outcomes of such reconstructions.Methods A literature review was performed using MEDLINE (PubMed), EMBASE, and the Cochrane Collaboration Library for research articles related to innervated free flaps in abdominal wall reconstruction.Results Nine case series (16 patients) were included who underwent free flap reconstruction of the abdominal wall with motor and/or sensory innervation. Reconstruction was performed with latissimus dorsi (n = 5), tensor fascia lata (n = 4), rectus femoris (n = 2), combined tensor fascia lata-anterolateral thigh (n = 2), combined vastus lateralis-tensor fascia lata-anterolateral thigh flaps (n = 2), and vastus lateralis-anterolateral thigh (n = 1). All but one reconstruction had motor neurotization performed (n = 15), while only 12.5% (n = 2) had sensory neurotization performed. At least 66.6% of patients (n = 10) who had motor neurotization regained motor function as evidenced by documented clinical examination findings while 93.3% (n = 14) had “satisfactory” motor function on author's subjective description of the function. Both flaps that had sensory innervation were successful with Semmes–Weinstein testing of 3.61.Conclusion A majority of neurotized free flap reconstructions for abdominal wall defects have been performed for motor innervation, which is almost invariably successful. Sensory neurotization has been carried out for a small number of these reconstructions, and also has been successful. Improvements in techniques and outcomes in innervated free flap abdominal wall reconstruction are important to advancing efforts in abdominal wall transplantation.
Keywords: abdominal wall reconstruction; anterolateral thigh flap; fasciocutaneous flap; free flap; innervated; innervation; neurotized; neurotization; plastic surgery; systematic review